Laser formation of luminescence bubble microstructures in polymer films. (September 2019) - Rybaltovskiy, A.O.; Akovantseva, A.A.; Burdukovskiy, V.F.; Krotova, L.I.; Minaev, N.V.; Timashev, P.S.; Holhoev, B.Ch.; Yusupov, V.I.
Abstract: The results of laser-induced formation of luminescent structures on the surface of poly-2.2'- n -oxydiphenylene-5.5'-bis-benzimidazole films, obtained by the coating method from a formic acid solution, are presented. The structures are formed using cw 405-nm laser radiation with intensities of 10 2 – 10 4 W cm –2 . It is shown (using methods of optical, atomic-force, and electron microscopy) that the structures formed on the surface are microbubble foam-like aggregations. Their formation is modelled as a sequence of the following processes: release of formic acid molecules, their condensation on matrix defects in the surface layer, and explosive boiling as a result of heating this layer of polymer film by the laser beam. The luminescence of these structures is due to the weakening of the concentration quenching from closely spaced luminescence centres in benzimidazole cycles during their emergence to the surface and the increase in the distance between them due to the extension on bubble aggregates on the surface.